Immunoelectrophoretic Analysis of Avian Ribonucleic Acid Tumor Virus Group-Specific Antigens - Bonar, R. A. (1972)
Tumors induced in pigeons by inoculation with the Schmidt-Ruppin strain of Rous sarcoma virus regressed after about 6 weeks. Sera from these pigeons, taken 8 weeks after inoculation, had complement-fixing group-specific antibody titers of 1:2 to 1:256. In immunoelectrophoresis with the pigeon serum, disrupted BAI strain A (myeloblastosis) avian tumor virus showed at least five precipitin arcs. The pattern of precipitin lines was dependent in part on the means used for virus disruption, and ethyl ether and nonionic detergents appeared to be both effective and relatively mild reagents. Immunoelectrophoretic comparison of pigeon serum with serum from a tumor-bearing hamster and that from virus-inoculated rabbits yielded similar, though not identical, results.